Estrus Induction Response Vis-a-Vis Serum Progesterone and estradiol 17-β Profile in Postpartum Subestrus Surti Buffaloes Primed with Heatsynch Alone and Heatsynch plus PRID Protocol - Saxena, Swati; Khastiya, CT; Savani, HR; Patel, MD; Tyagi, KK; Singh, VK (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was conducted on 18 subestrus Surti buffaloes at University farm to estimate steroid hormone values before, during and after use of Heatsynch (T1) and Heatsynch+PRID (T2) protocols. In the Heatsynch protocol (n=6), buffaloes were administered intramuscularly with inj. Busereline - GnRH analogue on day 0, inj. Cloprostenol sodium-PGF2α analogue on day 7 and inj. Estradiol Benzoate (EB-) on day 8. In the Heatsynch+PRID protocol (n=6), PRID was inserted intra-vaginally and kept in situ for 7 days with inj. Buserelineon day 0. The PRID was removed on day 7 together with inj. of Cloprostenol and inj. EB was administered on day 8. FTAI was done twice on day 10 in both the groups. No treatment was given to control (n=6) group (T3). The estrus response was 100% in all three groups, but the conception rate at first cycle/service was 50.00, 66.66 and 33.33%, respectively, in three groups. The mean plasma progesterone concentrations were significantly lower on day of estrus (0.26±0.05, 0.63±0.07and 0.58±0.08 ng/ml in T1, T2 and T3 respectively) as compared to the corresponding values on day 0, 4, 8 of treatment and 18 post-AI in all the three groups.The mean values of estradiol-17β markedly increased (p
Keywords: Estrus synchronization; Serum progesterone-estrogen; Subestrus; Surti buffaloes